The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Sydpolen på tvers - Høibakk, Ralph (Gyldendal, 1991)
Keywords: Antarktis; Den Norske Sydpolekspedisjonen 1990; Sydpolen; ekspedisjoner; reiser; reiseskildringer

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Predatory feeding behavior of an Antarctic marine copepod, Euchaeta antarctica - Yen, Jeannette (Polar Research, 1991)
Keywords: Antarktis; fytoplankton; hoppekreps; marin biologi